Fundamentals of Entrepreneurship (ENT300) Business Plan : AA Pod Systems Enterprises / Mohd Akmal Ahmad - Ahmad, Mohd Akmal (2015)
AA Pod Systems Enterprise offers pod systems product to customer – a new brand of unique, high-end devices, designed with functionality, beauty, and ease of use in mind, with good quality and affordable prices. Target market for our business pod systems is both genders. It’s because, AA Pod System’s goal is to deliver an unprecedented user experience to every customer, and to let our values shine through their products. Our business focuses more in Kedah on the market as it's the owner 's position that can easily be purchased by the consumer. In order to complain or provide feedback about our product, clients can also easily reach the company. With a true passion for craftsmanship and engineering, every product from AA Pod Systems fuses unique visuals with cutting-edge technology to create an exclusive product line. In 2014, the vape industry was still in its infancy. It was an open market, inviting an adventurous group of avid vapers and entrepreneurs to develop game changing devices with innovation and a unique vision. Akmal Ahmad was one of those innovators, and he established AA Pod Systems. 2018 has being the year of the vape pod system. AA Pod Systems has designed something revolutionary. The Orion DNA GO was this accomplishment. The first DNA chipset pod system available, the Orion has created a lot of noise and assured everyone that AA Pod Systems is always on top when it comes to innovation, design, and quality.